2017
DOI: 10.1242/dev.150763
|View full text |Cite
|
Sign up to set email alerts
|

Apical constriction is driven by a pulsatile apical myosin network in delaminating Drosophila neuroblasts

Abstract: Cell delamination is a conserved morphogenetic process important for the generation of cell diversity and maintenance of tissue homeostasis. Here, we used Drosophila embryonic neuroblasts as a model to study the apical constriction process during cell delamination. We observe dynamic myosin signals both around the cell adherens junctions and underneath the cell apical surface in the neuroectoderm. On the cell apical cortex, the nonjunctional myosin forms flows and pulses, which are termed medial myosin pulses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 46 publications
2
59
1
1
Order By: Relevance
“…In 46% of apical constriction phases, the closest maximal accumulation of medial MyoII in time preceded apical reduction within 45 sec ( Fig.2L). Together, these data suggest that pulses of apical-medial MyoII drive apical constriction in epi-NSCs, as previously observed in several other epithelia (Martin et al, 2009;Martin and Goldstein, 2014), including in the embryonic neuroectoderm during NSC delamination (Simões et al, 2017;An et al, 2017).…”
Section: Apical Constriction By Medial Myosin In Epi-nscssupporting
confidence: 83%
See 1 more Smart Citation
“…In 46% of apical constriction phases, the closest maximal accumulation of medial MyoII in time preceded apical reduction within 45 sec ( Fig.2L). Together, these data suggest that pulses of apical-medial MyoII drive apical constriction in epi-NSCs, as previously observed in several other epithelia (Martin et al, 2009;Martin and Goldstein, 2014), including in the embryonic neuroectoderm during NSC delamination (Simões et al, 2017;An et al, 2017).…”
Section: Apical Constriction By Medial Myosin In Epi-nscssupporting
confidence: 83%
“…Each NSC has a unique spatial identity that is provided in part by the segmentation genes (Urbach and Technau, 2003). As neuroectodermal cells become specified as NSCs, they undergo apical constriction driven by a pulsatile actomyosin meshwork (Simões et al, 2017;An et al, 2017;Sawyer et al, 2010;Martin and Goldstein, 2014). Concomitantly, Adherens Junctions (AJ) are disassembled as E-cadherin (E-cad) is removed from the apical-lateral membrane, leading to NSC ingression (Simões et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…NB delamination is driven by a pulsatile, actomyosin network localized apically in NB precursors, with Rho signaling important for medial myosin accumulation (An et al, 2017). This is in contrast to the removal of apoptotic or live cells by non-autonomous Rho signaling and multicellular actomyosin ring assembly (Figure 1).…”
Section: A Force For Good: Cell Extrusion In Development and Tissue Hmentioning
confidence: 99%
“…From this we hypothesised that expression of Notch intra not only reduces the number of neuroblasts, but also relieves the ventral epidermis from morphogenetic stress due to reduced neuroblast delamination. It has recently been shown that neuroblast delamination requires increased actomyosin activity ( An et al, 2017 ; Simões et al, 2017 ). In addition, studies from our lab have shown that Crb negatively regulates myosin contractility in the amnioserosa, thereby ensuring, among others, the maintenance of a proper adhesion belt ( Flores-Benitez and Knust, 2015 ).…”
Section: Resultsmentioning
confidence: 99%